The Dean's Report: The Law School: 1991–92 Academic Year - Dutile, Fernand N. (1992)
Acting Dean, Fernand N. Dutile, provides a description of the state of Notre Dame Law School as it closes the 1991–1992 academic year. The elements covered in his report include: administration, faculty, students, general comments, and priorities. Two addendums, both dated August 31, 1992 are the text of presentations on the State of the Law School, delivered by Tex Dutile, and The State of the Law Library, delivered by Janis Johnston. Supplementary reports are included from the Kresge Law Library, the National Institute for Trial Advocacy, the Thomas J. White Center on Law & Government, the Journal of College and University Law, the Center for Civil and Human Rights, the London Law Programme, the Notre Dame Law Review, and the Summer London Law Program